2016
DOI: 10.2147/ijn.s106540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cellular effects of starch-coated SPIONs and poly(lactic-co-glycolic acid) matrix nanoparticles on human monocytes

Abstract: Within the last years, progress has been made in the knowledge of the properties of medically used nanoparticles and their toxic effects, but still, little is known about their influence on cellular processes of immune cells. The aim of our comparative study was to present the influence of two different nanoparticle types on subcellular processes of primary monocytes and the leukemic monocyte cell line MM6. We used core-shell starch-coated superparamagnetic iron oxide nanoparticles (SPIONs) and matrix poly(lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…These cell-death proteases have high activity on specific target sequences (like Ala-Ala-Phe-R), different from the other intracellular proteases (like Gly-Phe-R) and for this reason the assay is very specific. Furthermore, the possibility to perform luminescence assay can reduce NPs interference Gonnissen et al, 2016;Iglesias et al, 2017;Zhang et al, 2017;Gurunathan et al, 2018 Cell proliferation (evaluation of mitotic rate)…”
Section: Colorimetrymentioning
confidence: 99%
“…These cell-death proteases have high activity on specific target sequences (like Ala-Ala-Phe-R), different from the other intracellular proteases (like Gly-Phe-R) and for this reason the assay is very specific. Furthermore, the possibility to perform luminescence assay can reduce NPs interference Gonnissen et al, 2016;Iglesias et al, 2017;Zhang et al, 2017;Gurunathan et al, 2018 Cell proliferation (evaluation of mitotic rate)…”
Section: Colorimetrymentioning
confidence: 99%
“…Similarly, PEG-coated IONPs increased reactive oxygen species (ROS), tumor necrosis factor alpha (TNFα), interleukin 1 beta (IL1β), and mitochondrial dysfunction in THP-1 human monocytes [67]. Another recent study reported that starch-coated IONPs alter subtle features, such as the cytoskeleton and ion channel functions, in monocytes without any apparent increase in IL1β and IL10 secretion [68]. In contrast, polyvinyl alcohol (PVA)–coated IONPs induced IL1β levels in monocytes without affecting the survival of these cells [69].…”
Section: Immunotoxicity Of Iron-based Nanoparticlesmentioning
confidence: 99%
“…After quantitative analysis, there was still a very low fluorescence signal around the tumour site after 5 days. In our previous work, we demonstrated that the self-assembled nanofibrils were excreted out of the tumour by hydrolysis 5 . Therefore, we speculated that the signal mainly came from the metabolite of the nanofibrils in tumour.…”
Section: Resultsmentioning
confidence: 98%
“…Traditional molecular chemotherapeutics and imaging agents exhibit relatively low bioavailability due to their fast metabolic clearance 1,2 . Nanomaterial systems with targeting motifs and optimized particle sizes accumulate within the tumour and have enhanced molecular utilization efficiency 35 . Numerous strategies, such as developing small nano-sized superstructures 6 , enhancing long-term circulation 4 , and using physical tools, have been pursued to increase the accumulation and retention of nanoparticles 7,8 , decrease toxicity and optimize metabolism 9,10 .…”
Section: Introductionmentioning
confidence: 99%